(3Sff CHj OGhO GdSLSJGfis - (3SdjeGf Hf GdCTYK Hf ESMGb Hf HTjQ GdCROj GdSLSJGfj, CHh OGhO,J (B275 (3g` s
(3ChdgG (B:s
(3CNHQfG CHh MaU YeQ Hf eMeO (B,,,, (3GHf WHQRO bGd MOKfG CHh OGhO bGd (B: (3cJGH GdWgGQI s
(3BNQgG (B:s
(3jbhd Gddg YR hLd (B: (3jDPjfi GHf BOe , jSH GdOgQ hCfG GdOgQ BNQ cJGH GdCOH hgh BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG HYV GdChQGb HNW eZGjQs
(3HgG fXGe GdJYbjHIs
(3QhGjI CHj MaU YeQ Hf WHQRO Yf CHj GdaJM eadM Hf CMeO GdOhei Yf CHj Ydi eMeO Hf CMeO GddDdDi Yf CHj OGhO s
(3YdjgG SeGYGJ HYVgG SfI (B604 (3hGdfSNI ai (B32 (3LRAkG MOjKkG s
(3hhVYJ HYV GdCLRGA ai ZjQ eMdgG s
Keywords: (3GdMOjK h GdeUWdMs